A Study on the quality control mechanisms in the manufacture of a purgative drug from the seeds of the Niog-niogan plant - Payumo, Jaymond S. (College of Engineering, 1987)
In a survey conducted at the Elsie Gaches Village in March, 1986, 106 out of 234 residents examined were clinically diagnosed to have intestinal parasites. As a result of current interest in herbal medicine, an attempt was made to document the effects of a new drug which have purgative qualities. A total of 40 patients were randomly treated with the drug. Patients were treated once a day for 3 to 5 days followed by a 7-14 day rest and recovery period. All patients were positively cured and their parasite content diminished by 85% or more. The purgative drug which comes from Niog-Niogan plant should be properly selected, cleaned, and sterilized because of the delicate results expected from the medication. The report will establish the control standards which will make the process effective.